The Association of Chronic Kidney Disease with Increased Cardiovascular Morbidity and Mortality: A Systematic Review - Calista Giovani; Charles Sanjaya Seikka (The Indonesian Journal of General Medicine, 2025)
INTRODUCTION: Chronic Kidney Disease (CKD) represents a global public health crisis, affecting over 10% of the world's population. It is now unequivocally recognized not merely as a renal condition but as a systemic state of exceptionally high cardiovascular risk, where patients are more likely to die from cardiovascular complications than to progress to end-stage kidney disease. This review systematically synthesizes the evidence quantifying this profound risk. METHODS: A systematic review of prospective cohort studies and meta-analyses published between January 2000 and September 2024 was conducted using PubMed, EMBASE, and the Cochrane Library. Studies were included if they reported on the association between CKD, defined by estimated glomerular filtration rate (eGFR) or albuminuria, and specific cardiovascular morbidity or mortality outcomes in adult populations. The risk of bias in included non-randomised studies was systematically assessed using the Cochrane ROBINS-I (Risk Of Bias In Non-randomised Studies - of Interventions) tool. RESULTS: A total of 18 prospective cohort studies and 3 meta-analyses, encompassing a collective population of over 5 million participants, met the inclusion criteria. The evidence demonstrates a strong, independent, and graded association between declining eGFR and increasing albuminuria with heightened risks for all-cause and cardiovascular mortality. Significant associations were confirmed for over 15 distinct outcomes. Compared to preserved renal function, CKD was associated with substantially increased risks for myocardial infarction (Hazard Ratio up to 1.90), ischemic and hemorrhagic stroke (HR up to 2.19), incident heart failure (HR >2.0 for severe CKD), atrial fibrillation (HR up to 4.04 in stage 4 CKD), peripheral artery disease (HR >6.0 for associated complications), and sudden cardiac death, for which CKD confers a risk 4 to 20 times greater than that of the general population. DISCUSSION: The profound cardiovascular risk in CKD is driven by a synergistic interplay of highly prevalent traditional risk factors (e.g., hypertension, diabetes) and potent, non-traditional uremia-specific pathways. These include chronic inflammation, oxidative stress, sympathetic overactivity, anemia, and CKD-Mineral and Bone Disorder (CKD-MBD), which leads to accelerated and extensive vascular calcification. This unique pathophysiology renders general population risk scores inadequate and necessitates an integrated, cardiorenal-metabolic approach to patient management, as advocated by modern clinical practice guidelines. CONCLUSION: The evidence is overwhelming and definitive: CKD is a potent and independent risk multiplier for a wide spectrum of fatal and non-fatal cardiovascular events. Aggressive risk stratification using both eGFR and albuminuria, coupled with intensive management of both traditional and CKD-specific risk factors, is imperative to mitigate this substantial burden of disease.